2021
DOI: 10.1111/cga.12432
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the maternal levels of serum proprotein convertase subtilisin/kexin type 9 in pregnant women with the complication of fetal open neural tube defects

Abstract: It was aimed to evaluate the levels of maternal serum proprotein convertase subtilisin/ kexin type 9 (PCSK9) in pregnant women with a fetus diagnosed with open neural tube defects (NTDs). This case-control study included 38 pregnant women carrying fetuses with open NTDs and 44 age-matched, pregnant women with no specified risk factors.Comparisons were made of the groups in respect of demographic and clinical data and PCSK9 levels. To examine the performance of PCSK9 levels in the prediction of fetal open NTDs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Although it has limitations, PCSK9 may be used as an additional biomarker for the screening of NTDs. 6 Several studies have reported various risk factors linked to anencephaly, which include socioeconomic status, parental education, maternal age and occupation, smoking, alcoholism, maternal reproductive history, infection during early pregnancy, diabetes, obesity, and maternal use of caffeine and medications during early pregnancy. [7][8][9] The prevalence of anencephaly shows great variation among different countries, with 12 per 10,000 births in Iran, 10 10.4 per 10,000 births in China, 0.00-7.42 per 10,000 births in Rijeka, Croatia, 11 0.5-0.6 per 1000 live births in Singapore 12 and 0.5-6.5 per 1000 live births in India.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has limitations, PCSK9 may be used as an additional biomarker for the screening of NTDs. 6 Several studies have reported various risk factors linked to anencephaly, which include socioeconomic status, parental education, maternal age and occupation, smoking, alcoholism, maternal reproductive history, infection during early pregnancy, diabetes, obesity, and maternal use of caffeine and medications during early pregnancy. [7][8][9] The prevalence of anencephaly shows great variation among different countries, with 12 per 10,000 births in Iran, 10 10.4 per 10,000 births in China, 0.00-7.42 per 10,000 births in Rijeka, Croatia, 11 0.5-0.6 per 1000 live births in Singapore 12 and 0.5-6.5 per 1000 live births in India.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the safety of using PCSK9i during pregnancy is yet to be clearly established, particularly as PCSK9i has been shown to cross the placental barrier (18). Our prior research as well as a recent study identi ed lower PCSK9 expression in the serum of pregnant women with NTD fetuses (12,15), assuming that NTDs could be possible side effects among pregnant women exposed to PCKS9i. However, there is no evidence to manifest the safety of PCSK9i with regard to foetal NTDs.…”
Section: Discussionmentioning
confidence: 75%
“…NTDs, which occur following failure of neural tube closure during the fourth week of embryonic development, are among the most common and devastating congenital anomalies of the central nervous system (13). Typical NTDs include spina bi da, anencephaly, and exencephaly, according to the location and severity of the lesion, which pose huge medical, nancial, and psychological costs on affected families (14).. A more recent study con rmed that reduced PCSK9 in maternal serum is a potential biomarker for human pregnancies with open NTDs (15). PCSK9 is expressed in the brain at certain crucial stage during embryonic neurulation, which is a key time point in NTD formation (2,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…A previous epidemiological study of NTDs also showed that isolated NTDs were more sensitive to environmental factors, whereas non-isolated NTDs were sensitive to both environmental and genetic factors [ 30 ]. In addition, some biomarkers are also considered to play an important role in NTD screening during pregnancy, such as maternal serum alpha-fetoprotein (MSAFP) [ 31 ] and proprotein convertase subtilisin/kexin type 9 (PCSK9) [ 32 ]. However, whether the same biomarkers are equally predictive for screening isolated NTDs and non-isolated NTDs needs further research.…”
Section: Discussionmentioning
confidence: 99%